Softening the corrective effect of populism: populist parties' impact on political interest - Miroslav Nemčok; Constantin Manuel Bosancianu; Olga Leshchenko; Alena Kluknavská (West European Politics, 2022)
Populist appeals to `pure people' have been theorised to mobilise previously disengaged citizens. However, this `corrective consequence' has found weak support in empirical research. This finding is consistent with studies that suggest that novel campaign appeals and new political offerings have a negligible effect on turnout. As a consequence, this research proposes a distinction between the behavioural and attitudinal effects of populism and introduces a softened revision to the corrective argument: Despite a negligible behavioural impact on individuals' turnout propensity, the electoral success of populism is nevertheless associated with an attitudinal change: increased political interest. This proposition is supported by two empirical tests. The first detects this dynamic among 232,208 respondents in 136 national election studies from 16 Western countries (1970–2017). The second analysis, which uses an improved causal identification strategy, uncovers an analogous effect in the GESIS Panel (2014–17, Germany). Hence, the emergence of populist parties can stimulate political interest among citizens, even though it does not necessarily lead to increased turnout.
doi:10.6084/m9.figshare.20348351.v1
Keywords: 320; corrective effect of populism; political parties; political interest; voter attitudes